Legal Effects of Land Abandonment in the Perspective of Justice Theory - Siswanto, Cecep Tedi (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
This research was conducted with the aim of knowing and analyzing the legal consequences of land abandonment in the perspective of justice theory. Abandoned land, especially land that is deliberately abandoned and not used by land rights holders does not reflect the principle of justice for the state and society in the social function of land rights, so the state must put it in order. This research is a normative juridical research with a statute approach. The results showed that the legal consequences of land abandonment can lead to the abolition of Land Rights or Management Rights. In addition, it can also cause legal relations and affirmation as state land former Abandoned Land directly controlled by the state. The results showed that the legal consequences of land abandonment can lead to the abolition of Land Rights or Management Rights. In addition, it can also cause legal relations and affirmation as state land former Abandoned Land directly controlled by the state. The legal consequences in terms of the theory of justice have fulfilled the values of justice because the regulation of abandoned land is not carried out unilaterally, but still involves the role of Rights Holders, Management Rights Holders, or Basic Land Tenure Holders.